2018
DOI: 10.13057/biodiv/d190142
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and habitat characteristics of macrozoobenthos in the mangrove forest of Lubuk Kertang Village, North Sumatra, Indonesia

Abstract: asyuni M, Gultom K, Fitri A, Susetya EA, Wati R, Slamet B, Sulistiyono N, Yusriani E, Balke T, Bunting P. 2018. Diversity and habitat characteristics of macrozoobenthos in the mangrove forest of Lubuk Kertang Village, North Sumatra, Indonesia. Biodiversitas 19: 311-317. Mangrove plays an important role in coastal ecosystems including ecological, social, and economic aspects. This study aimed to determine the diversity of macrozoobenthos and water quality based on diversity index (H’), similarity Index (E), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
1
29
1
3
Order By: Relevance
“…Infaunal species such as T. sulcarius are collected in locations where the texture of the substrate often mixes with the sand that allowing this species to burrow (Masangcay and Lacuna 2017). Macrozoobenthos from classes of gastropod and bivalve tended to be found in the sand substrate type (Basyuni et al 2018). The texture of sandy clay substrate was suitable for the life of M. meretrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infaunal species such as T. sulcarius are collected in locations where the texture of the substrate often mixes with the sand that allowing this species to burrow (Masangcay and Lacuna 2017). Macrozoobenthos from classes of gastropod and bivalve tended to be found in the sand substrate type (Basyuni et al 2018). The texture of sandy clay substrate was suitable for the life of M. meretrix.…”
Section: Discussionmentioning
confidence: 99%
“…Low categorization of Evenness index indicated that individual distribution was not equal and there was a tendency for a community to be dominated by particular species (Basyuni et al 2018). High Evenness Index in a community showed that the number of individuals of each species was almost the same and there were no dominating species.…”
Section: Discussionmentioning
confidence: 99%
“…Ekosistem hutan mangrove merupakan habitat berbagai jenis mikroorganisme yang toleran terhadap keadaan lingkungan ekstrim (Retnowati et al, 2017), yang berperan dalam melestarikan keanekaragaman hayati (Dharmawan et al, 2016). Ekosistem mangrove dihuni oleh berbagai jenis biota baik hidup di perairan atau dari darat ke arah laut (Basyuni et al, 2018), hal ini disebakan karena ekosistem mangrove termasuk tipe ekosistem yang tidak terpengaruh oleh iklim, tetapi faktor lingkungan yang sangat dominan dalam pembentukan ekosistem. Mangrove dibatasi oleh suhu secara global, akan tetapi variasi curah hujan, salinitas, pasang surut, gelombang, dan arus sungai sangat menentukan hamparan atau luasan dan biomassa mangrove pada skala regional dan lokal (Alongi, 2008).…”
Section: Pendahuluanunclassified
“…Mangroves are important for preserving biodiversity, as well as for providing wood and non-wood products to local communities (Dharmawan et al 2016). Mangrove ecology consists of various organisms, both living on land and in the water (Basyuni et al 2018). Mangroves also protect small fishes and the larvae of fishes and clams, guarding them against predators (Lapolo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves also protect small fishes and the larvae of fishes and clams, guarding them against predators (Lapolo et al 2018). All these make mangroves very important elements in coastal ecosystems, in various aspects including ecological, social, and economical (Basyuni et al 2018). Mangroves are globally limited by temperature.…”
Section: Introductionmentioning
confidence: 99%